Propofol Use in Emergency Surgery in a Patient Having Alcohol Withdrawal - Sandeep Grover; Chandrima Naskar; Kajal Jain; Sameer Aggarwal (Annals of Indian Psychiatry)
Alcohol use disorder is a common mental health issue with life-threatening consequences like sustaining polytrauma while driving under the influence of alcohol. Such patients frequently require surgical interventions. Because of the alcohol dependence, they have a high risk of developing alcohol withdrawal (including delirium tremens) immediately before or sometimes after the surgery. No clear guidelines exist regarding the choice of anesthetic agent in this special population, even though the diagnosis of alcohol withdrawal and/or delirium can affect the outcome of the surgical intervention in multiple ways. At times, the anesthetic agent used during the surgical procedure can delay the onset of alcohol withdrawal delirium in these patients, in the postoperative period, thus complicating its identification and management. In this report, we present two scenarios in which the presence of alcohol withdrawal symptoms in the perioperative period was markedly affected by the use of infusion of propofol during the surgery. We also discuss how the mindful use of propofol infusion for anesthesia and analgesia during surgery can be a useful method, in addition to the usual benzodiazepine-based management, in this specific population to reduce the consequences of alcohol withdrawal in the postoperative period.